Space charge in liquid argon time-projection chambers: a review of analytical and numerical models, and mitigation methods - Palestini, S.; Resnati, F. (Journal of instrumentation, 2021)
The subject of space charge in ionisation detectors is reviewed, with particular attention to the case of liquid argon time projection chambers. Analytical and numerical description of the effects on the reconstructed coordinates along the drift and the transverse directions are presented. The cases of limited electron lifetime, of dual-phase detectors with ion feedback, and of detectors with small and comparable ratio between drift length and width are considered. Two design solutions that mitigates the effects are discussed.